An Analysis Of Feminist Thoughts Of Life’s Struggle Presented In The Movie “Little Woman (2019)” - Rara Pramudhita Nurani Putri; Abdillah Nugroho (Green Publisher Indonesia, 2024)
Modern women frequently encounter challenges in their perspectives on life's struggle, such as focusing on social expectations of women, experiencing a lack of spiritual support in relationships, and facing a disconnection between education, job, and marriage, which hinders their pursuit of an ideal partnership. This research examines the life of education, marriage experiences, ideas, and inspirations of Jo March in the movie